2011
DOI: 10.1111/j.1748-1090.2011.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Could sexually experienced Gorillas Gorilla gorilla gorilla help hand-reared Gorillas to breed successfully?

Abstract: To maintain a self‐sustaining European Endangered Species Programme (EEP) population of Gorillas Gorilla gorilla gorilla, it is necessary that as many individuals as possible contribute their genes to the population. It is believed that hand‐rearing may prevent the development of a good repertoire of natural social behaviours that would facilitate successful breeding when individuals reach sexual maturity. Between 1980 and 2004, 464 Gorilla births resulted in 117 individuals [63.54 (♂.♀)] being hand‐reared. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The majority of studies on the effects of hand-rearing in relation to reproductive success have focused on non-human primates. For example, hand-reared western lowland gorillas ( Gorilla gorilla gorilla ) had lower breeding success than mother-reared gorillas and were less likely to breed with other hand-reared individuals [ 4 , 18 , 19 , 20 , 21 ]. Some studies on carnivores have begun to show that hand-rearing affects their behaviour and reproductive success as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies on the effects of hand-rearing in relation to reproductive success have focused on non-human primates. For example, hand-reared western lowland gorillas ( Gorilla gorilla gorilla ) had lower breeding success than mother-reared gorillas and were less likely to breed with other hand-reared individuals [ 4 , 18 , 19 , 20 , 21 ]. Some studies on carnivores have begun to show that hand-rearing affects their behaviour and reproductive success as well.…”
Section: Introductionmentioning
confidence: 99%
“…As parental rearing positively impacts future reproductive success of gorilla offspring, the gorilla SSP is placing a strong emphasis on the management protocols that encourage maternal competence before and after the actual birth of an infant [ 4 ]. There is a reproductive skew present in gorillas due to rearing type [ 4 , 18 , 19 , 20 , 21 ] and evidence of a similar trend in domestic cats as well [ 23 ]. Research has shown that hand-reared gorillas have fewer opportunities to reproduce.…”
Section: Introductionmentioning
confidence: 99%
“…Males, and especially those who are genetically important for the population, have to remain in their natal groups as long as possible, at least until the age of 10–12 years (Abelló et al ., ). This will not only improve their social skills but also it is a way to decrease the number of surplus ♂♂.…”
Section: Management Of the Populationmentioning
confidence: 97%
“…Recent research has shown that there is a higher chance for breeding when genetically important ♂♂ that may have a reproductive behavioural deficit or are suspected to be infertile are placed with experienced breeding ♀♀ (Abelló et al ., ). Psychological factors and a mate showing natural behaviour seem to play an important role in the chance of achieving positive outcomes.…”
Section: Development Of the Populationmentioning
confidence: 97%
See 1 more Smart Citation